High step‐up cascaded DC–DC converter integrating coupled inductor and passive snubber. Issue 9 (12th July 2019) - Pan, Quanyou; Liu, Hongchen; Wheeler, Pat; Wu, Fengjiang
Abstract : A new high step‐up cascaded DC–DC converter is proposed in this study, which is composed of one cascaded boost converter, one diode–capacitor structure and a coupled inductor with extended voltage‐doubling cell. The proposed converter can achieve high‐voltage gain by adjusting the duty cycle and the turns ratio of the coupled inductor, which avoids the circuit operating at the extreme duty cycle. Moreover, a passive clamped circuit is utilised to decrease the voltage stresses on the power devices and absorb the energy of leakage inductance of the coupled inductor to increase voltage gain. Thus, it reduces the conduction losses and alleviates the reverse‐recovery problem of diodes. In conclusion, the proposed converter can achieve high‐voltage gain and improve efficiency. The operating principle and steady‐state analysis of the proposed converter is illustrated in detail in this study. Finally, experimental results of a prototype circuit with input voltage 40 V, output voltage 300 V and output power 200 W are presented to verify the analysis results of the proposed converter.